The Role of Instagram in Improving The Reputation of Private Hospitals - Lestari, Eni; Andhita Sari, A; Rizki Pratama, Muhammad (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The shift in people's habits is influenced by the development of technology. Social media is the most effective tool to convey messages to the public. Instagram is the best choice for private hospitals to promote themselves. Instagram features are able to attract public attention to increase public interaction with the hospital. The purpose of the research is to find out how the role of Instagram in improving the reputation of private hospitals in the city of Surakarta. The method in this study is descriptive qualitative with a content analysis approach of the interactions that occur and the content patterns of the three private hospitals JIH, Indriati, and Kasih Ibu in the time frame of October - December 2023. Using Herbert Baum's Reputation theory related to 4 aspects: reliability where the hospital provides the best service according to public expectations through content uploads. Trustworthiness where the community believes from content uploads and interactions and a sense of pride in doing treatment. Responsibility where the hospital responds quickly to incoming feedback via inbox or Instagram comments. Credibility where the hospital is able to show reliability in service through content uploads. The four aspects of reputation can be seen through engagement like, viewer, repost, and comment. Through these content uploads, the hospital's reputation is positive. The content typology of the three private hospitals is grouped into 3 namely educational content, promotion and publication where the three types of content are able to improve the reputation of private hospitals.